2021
DOI: 10.4102/jef.v14i1.655
|View full text |Cite
|
Sign up to set email alerts
|

Mobile money and regional financial integration: Evidence from sub-Saharan Africa

Abstract: Orientation: The article examines the impact of mobile money adoption and regional financial integration in sub-Saharan Africa.Research purpose: The study sought to uncover the relationship between mobile money adoption and cross-border remittances as a de facto measure of regional integration.Motivation for the study: The extent to which differences in mobile money penetration rates across sub-Saharan Africa influence cross-border remittances remains a grey area that necessitates empirical investigation.Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Akhmadi (2019), in his inflation has no significant effect on electronic money. (Kipkemboi & Bahia, 2019), in their research, stated that inflation has no effect on cellular money in Nigeria.…”
Section: Introductionmentioning
confidence: 97%
“…Akhmadi (2019), in his inflation has no significant effect on electronic money. (Kipkemboi & Bahia, 2019), in their research, stated that inflation has no effect on cellular money in Nigeria.…”
Section: Introductionmentioning
confidence: 97%
“…They noted that mobile money services in Uganda had signi cant welfare bene ts, providing access to affordable nancial services and helping to reduce poverty and vulnerability among rural populations, thereby promoting nancial inclusion. In their study, Tembo and Okoro (2021) reported that Uganda and Rwanda ranked second after Kenya in terms of high mobile money account penetration rates, at 67% and 57%…”
Section: Introductionmentioning
confidence: 99%